Consumption of osmo-dehydrated Andean Berry (Vaccinium meridionale Swartz) decreases levels of pro-inflammatory biomarkers of overweight and obese adults - Gallego Peláez, Emerson; Maldonado Celis, María Elena; Posada Jhonson, Luz Gladys; Gómez García, Ana Cristina; Torres Camargo, David (Vitae, 2021)
Background: A Body Mass Index (BMI) greater than 24.9 Kg/m2 promotes chronic inflammation due to increased secretion of pro-inflammatory adipokines. Consuming fruits rich in bioactive compounds such as berries is a promising strategy to counteract this effect. Objectives: Determine the effect of osmo-dehydrated Andean Berry consumption on inflammatory biomarkers (TNF-α, IL-6, IL-1β, and adiponectin) and plasma antioxidant capacity in overweight and obese adults after 21 days. Methods: Andean Berry was osmo-dehydrated in 70% sucrose syrup. Antioxidant activity, proximal composition, phenolic content, microbiological analysis, and sensory analysis of the product were determined. Twenty-five obese and overweight subjects consumed 35g of osmo-dehydrated berry for 21 days. Inflammatory biomarkers and antioxidant capacity in plasma were evaluated at the beginning and end of the study. Results: Osmo-dehydrated Andean Berry presented a total phenolic content of 692.7 ± 47.4 mg Gallic Acid Equivalents/100 g. All biomarkers evaluated in the subjects showed statistically significant differences (p> 0.05), except for CRP, before and after the study. IL-6 presented the more significant reduction among all pro-inflammatory adipokines with an effect size of 18.4 Conclusions: Regular consumption of osmo-dehydrated Andean Berry contributes to decreasing pro-inflammatory biomarkers and improves the plasma antioxidant capacity of overweight and obese adults.